The Implications of Debt Heterogeneity for R&D Investment and Firm Performance - David, Parthiban; O'Brien, Jonathan P.; Yoshikawa, Toru (Academy of Management Journal, 2008)
An assumption in prior research is that debt is homogeneous and provides inappropriate governance for R&D investments. We argue that debt is heterogeneous: although transactional debt does indeed impose strict contractual constraints that provide inappropriate governance for R&D investments, relational debt has very different characteristics that provide more appropriate governance. Using a sample of Japanese firms, we find that firms that align their debt structures with their R&D investments perform better than those that are misaligned. Furthermore, firms tend to align their debt structure with R&D investments, but only after deregulation permits relatively free access to various types of debt.